1983
DOI: 10.1080/00986448308940293
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Porous Media on the Flow of Polymer Melts in Capillaries†

Abstract: porous media placed in the entrance of capillaries were found to reduce the pressure drop across the capillaries (t>P,) by a factor of two or three for polystyrene. The reduction in t>P, was found to be a function of the distance of the porous media from the capillary entrance, the type of porous media, the length of the capillary, and the rheological properties of the polymer melt. No significant reduction in t>P, was observed for a polymer melt such as polyethyleneterephthalare (PET) which is nearly devoid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Therefore, when the temperature increases, the viscosity is lower and the critical stress is reached for a higher flow rate. As in the case of the oscillating defect, the presence of upstream filters stabilizes the flow and delays the onset of volume defects, but always at the expense of an increase in pressure (Done et al, 1983;Piau et al, 2000;Goutille and Guillet, 2002a). It seems that the disentanglement of the polymer chains when passing through the filters can explain this effect (Goutille and Guillet, 2002b).…”
Section: Remedies and Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when the temperature increases, the viscosity is lower and the critical stress is reached for a higher flow rate. As in the case of the oscillating defect, the presence of upstream filters stabilizes the flow and delays the onset of volume defects, but always at the expense of an increase in pressure (Done et al, 1983;Piau et al, 2000;Goutille and Guillet, 2002a). It seems that the disentanglement of the polymer chains when passing through the filters can explain this effect (Goutille and Guillet, 2002b).…”
Section: Remedies and Solutionsmentioning
confidence: 99%
“…As previously, some solutions, efficient at the laboratory scale, are not necessarily useful at the industrial level. For example, some authors (Done et al, 1983;Piau et al, 2000;Goutille and Guillet, 2002a) have proposed to install filters upstream of the die. It can be seen in Fig.…”
Section: The Descriptive Modelsmentioning
confidence: 99%
“…However, Den Otter [17] underlined that the oscillations of the strand are of lower amplitude and higher frequency through the conical die as for the die with flat entrance. Another possibility studied by Done et al [19] and Piau et al [20] was to dispose of different kinds of porous media at the entrance of the die in order to diminish the elongational rates imposed on the flowing polymer in this contraction zone. Concerning Done et al [19] they studied the extrusion of a polystyrene (PS) and a polyethylene terephtalate (PET) through different axisymetric dies.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility studied by Done et al [19] and Piau et al [20] was to dispose of different kinds of porous media at the entrance of the die in order to diminish the elongational rates imposed on the flowing polymer in this contraction zone. Concerning Done et al [19] they studied the extrusion of a polystyrene (PS) and a polyethylene terephtalate (PET) through different axisymetric dies. They showed that the addition of porous media in the entry region was found to obviously increase the total pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, extrusion of polymer melts at high extrusion speed encounters various extrusion defects such as sharkskin, stick-slip and gross melt fracture, as clearly identified in the review by Petrie and Denn. 1) Considering the effect of filter or porous medium, it is interesting to note that the addition of filter or porous medium at the entrance of contraction can mitigate the gross melt fracture defect [2][3][4] , thus increases the possible speed for the process. However the mechanism of the phenomenon has been poorly understood yet, and further investigation is required.…”
Section: Introductionmentioning
confidence: 99%